РОЛЬ ИНОСТРАННЫХ ИНВЕСТИЦИЙ В СТРАНАХ С ТРАНСФОРМИРУЕМОЙ ЭКОНОМИКОЙ - Оруджева, М Ш (Journal of Economic Research & Business Administration, 2015)
In the article the role of foreign investments into economy of the Former Soviet Republics is considered. The dynamics of investments into the countries of EvrAzES and Azerbaijan is analyzed, dynamics and structure of investments into a fixed capital on sources for 2000-2008 is described, the share of internal and external investments is compared.